Perilaku Keagamaan Santri Lanjut Usia(LANSIA) di Pondok Pesantren Sepuh Masjid Agung Payaman Magelang - Imam Machdali; Mangun Budiyanto (Universitas Islam Indonesia, 2014)
This article aims to study the religious behavior of elderly studentsin Islamic boardingschool of Sepuh Payaman Magelang. analysis in this study is through the fivedimensions; religious belief (ideological), religious practice (ritualistic), religious knowledge (intellectual), religious appreciation (experiential), and experience religion (consequential). The results of this study showed that the ideological dimension embodied in the belief of the pillars of faith in the form of full submission to God as the One single, unified set of all creatures on lafadz tahlil